How Might World Heritage Status Support the Protection of Sacred Natural Sites? An Analysis of Nomination Files, Management, and Governance Contexts - Verschuuren, Bas; Ormsby, Alison; Jackson, Wendy (Land (Basel), 2022)
This study provides an overview of how sacred natural sites are given recognition within the World Heritage system. It offers an analysis of the extent to which sacred natural sites that are part of nine World Heritage sites are recognised in site nomination files, management plans, and governance of these sites. The World Heritage sites are located across all continents except for Antarctica. We analysed sites in Australia, Greece, Guatemala, India, Japan, Kenya, Malaysia, New Zealand and the Russian Federation. We found that the cultural and spiritual significance of sacred natural sites is under-recognised, especially in natural World Heritage sites. In addition, Indigenous and religious custodians are frequently excluded from site management and governance. We make four recommendations for improving the recognition of sacred natural sites and the involvement of their custodians in the World Heritage process and in site nomination, governance, and management: (1) identification and recognition of sacred natural sites including their associated cultural and spiritual values; (2) recognition of, and articulated roles for custodians of sacred natural sites in the governance and management of World Heritage sites; (3) increased uptake of religious groups and Indigenous Peoples’ conservation approaches to the joint management of World Heritage sites that contain sacred natural sites, and (4) prevention of exclusion of custodians and ecological migration by applying inclusive conservation practices through rights-based approaches.